Effects of social deprivation and healthcare access on major amputation following a diabetic foot ulcer in a French administrative area: Analysis using the French claim data. Issue 6 (2nd March 2022) - Bonnet, Jean‐Baptiste; Nicolet, Guillaume; Papinaud, Laurence; Avignon, Antoine; Duflos, Claire; Sultan, Ariane
Abstract: Aim: The link between social deprivation and the development of diabetic foot ulcer (DFU) is still widely debated. The study objective was to evaluate the relationship between lower limb amputation, social deprivation level, and inequalities in access to care service among people with DFU. This regional pilot study was conducted at the living area level and based on the French National Health Data System (SNDS). Methods: We conducted a retrospective cohort study using hospital and primary care claim data in the Languedoc‐Roussillon region. DFUs were determined using an original algorithm of care consumption or hospital diagnosis. The primary end point was amputation at 1 year. Secondary end points were mortality at 1 year and impact of potential access to care on amputation. Results: We included 15, 507 people from 2015 to 2017. Amputation and mortality rates were 17.5 and 117 per 1000 person‐years. The least precarious living areas showed better prognoses (relative risk = 0.46; 95% CI 0.27–0.66). Territorial accessibility to a private‐practice nurse, unlike physician accessibility, was associated with better results on major outcomes ( p = 0.004). Conclusion: This is the first study using SNDS to study the care pathway of DFU management within and outside the hospital. High social deprivation in a living areas seems to be associated with more major amputations after a DFU.